2018
DOI: 10.1002/pbc.27503
|View full text |Cite
|
Sign up to set email alerts
|

Risk of avascular necrosis of the femoral head in children with sickle cell disease on hydroxyurea: MRI evaluation

Abstract: Background There are conflicting reports on the role of hydroxyurea (HU) in the pathogenesis of avascular necrosis of the femoral head (AVNFH) in patients with sickle cell disease (SCD). Procedure The present study is a prospective cohort study of Kuwaiti children with SCD who were treated with HU. They had magnetic resonance imaging of the hips before starting HU and at regular intervals during a follow‐up period, ranging from 1 to 15 years. Results There were 40 patients (18 SS, 19 Sβ0‐thalassemia, and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
2
12
1
Order By: Relevance
“…The prevalence of hip necrosis was comparable with previously published data, while the number of occult lesions of the vertebrae and humeri is surprisingly high. Bone infarcts may be present also in children without bone pain, with a consequent underestimate of these complications 6,7,23–26 …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hip necrosis was comparable with previously published data, while the number of occult lesions of the vertebrae and humeri is surprisingly high. Bone infarcts may be present also in children without bone pain, with a consequent underestimate of these complications 6,7,23–26 …”
Section: Discussionmentioning
confidence: 99%
“…Some reports postulated that HU can be a risk factor for OST given it increases HbF and hematocrit leading to increased blood viscosity and sickling in the microcirculation of the femoral head 13. However, a recent prospective study reported there is no evidence that HU therapy is a risk factor for avascular necrosis of the femoral head and that it may prevent new lesions and deter the progression of existing lesions 14. There is no evidence that supports the use of HU to treat or prevent OST.…”
Section: Discussionmentioning
confidence: 99%
“…We have followed many patients on HU for upwards of 15 years. Pre-and post-HU MRI of the hips have not suggested any increased predisposition to avascular necrosis of the femoral head; if anything, it tends to deter the appearance of new or progression of existing necrotic lesions [54,55,66].…”
Section: Response To Hydroxyurea In Kuwaiti Patientsmentioning
confidence: 99%